(untitled) (Bangladesh Journal of Medical Education, 2012)
Patient and the general people expect that doctors remain up-to-date and professionally competent. The formal undergraduate and postgraduate education and training are conducted to bring a behavioral change in a medical practitioner to meet that expectation. The rate and magnitude of change in medical science is such that the contents of text books are not sufficiently up-to-date rather somewhat out of date at the time of publication. CME is continuing education in knowledge and skill of medical practice through which doctors will remain up-to date. Due to rapid changes in health care delivery system; health professionals needs to transform from a continuing education (CME) to a continuous professional development (CPD) model so that they remain up-to-date in their knowledge and competency in total care. CPD is a broader concept for continuing development of multifaceted competencies inherent in medical practice including medical, managerial, social and personal subjects which are needed for high quality professional performance in modern health care delivery system. CPD is complementary to formal undergraduate and postgraduate education; completing the educational trilogy. Undergraduate and postgraduate medical education is regulated by specific rules and regulation but CPD is the process where the responsibility rests on professionals and individual doctor. People expect what is best rather than what is right for a particular situation and for that level; professional competence should be combined with improvisation and general oversight. That is why, all over the world the concept of CPD is emerging and developing as a dynamic educational process to improve and upgrade ones professional performance. As a part of the global resident we should be familiar to cope with and should be trying to contribute in these progress and development. This article will help us to initial understanding and formulating an approach to that. DOI: http://dx.doi.org/10.3329/bjme.v1i1.12857 Bangladesh Journal of Medical Education Vol.1(1) 2010 pp.37-44